ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PADA KEDAI SUSU MOMMILK CABANG MANAHAN DI SURAKARTA - Mawati, Lilis (Universitas Slamet Riyadi, 2015)
Purpose of this research to analyze effect of price, product, place, promotion and service on satisfaction of customers Mommilk Manahan Surakarta. Design research are case study at Mommilk Manahan Surakarta. Population are customers who come at Mommilk Manahan Surakarta. Sample use 50 customers with quota sampling technique. This type of data is qualitative data and quantitative data. Source of data used primary data and secondary Collected data technique use observation, documentation and questionnaires, Analysis technique use multiple linear regression. The result showed that price significance affect on customers satisfaction. Product has significance effect on customers satisfaction. Place has significance effect on customers satisfaction. Promotion has significance effect on customers satisfaction. Service has significance effect on customer satisfaction. Product are dominant effect on customer satisfaction. Keywords: price, product, place, promotion, service, satisfaction